PENGARUH LOKASI DAN KUALITAS PELAYANAN ISLAMI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI UNIT TOKO AUSATH GROSIR SEMBAKO KOPPONTREN AUSATH BLOKAGUNG - Ribut Suprapto; Durrotun Nafisah (Jurnal Ekonomi Syariah Darussalam, 2020)
The purpose of this study is 1) To determine the significant effect between location (X1) on purchasing decisions (Y). 2) To determine the significant influence of the quality of Islamic services on purchasing decisions (X2). 3) To find out the significant influence between location (X1) and the quality of Islamic services (X2) simultaneously or together on purchasing decisions (Y). The results of the multiple regression test obtained the coefficient price (rx1x2y) of 0.701 and the price of the coefficient of determination (rx1x2y) 2 of 49.140%. The F (rx1x2y) test results showed that the Fhitung was 13.046 and the Ftabel at the 5% level was 3.35. T test results are known that thitung shows that the figure is greater than ttabel or 13,046 > 3.35 so that there is a significant influence between the location and quality of Islamic services simultaneously on consumer purchasing decisions in Ausath Grocery Grocery Unit Unit at Ausath Blokagung Banyuwangi Regency. This means that each independent variable, namely location and quality of Islamic services, has a significant simultaneous effect on the dependent variable (consumer purchase decision) in the Ausath Grocery Store Unit of Ausath Blokagung Koppontren, Banyuwangi.